Unveiling the financial pathway to human development: insights from non-linear ARDL and Granger causality analysis - Hafiz M. Sohail; Mirzat Ullah; Muhammad Shahzad Nazir; Canqing Tang (Humanities & Social Sciences Communications)
Abstract The current study examines the relationship between financial inclusion, encompassing key indicators such as financial access, depth, efficiency, and stability, and the Human Development Index (HDI) within the BRICS economies (Brazil, Russia, India, China, and South Africa). Using the annual data from 2004 to 2022, this study employs Panel Auto Regressive Distributed Lag (ARDL), Panel non-linear ARDL, and Feasible Generalized Least Squares (FGLS) estimation techniques to explore both linear and non-linear dynamics. Notably, both symmetric and asymmetric (positive shocks) of these financial indicators demonstrate a substantial and positive connectedness with improvements in HDI. Moreover, the analysis reveals the contributive roles of urbanization and internet usage in the models, reinforcing their significance in driving HDI. The study further establishes a Granger causal relationship between financial inclusion indices and HDI, highlighting the causal association of these dimensions. This study offers practical policy implications, emphasizing that HDI is pivotal in fostering socio-economic advancement within the BRICS bloc. It underscores the indispensable role of financial inclusion in promoting sustainable development and inclusive growth trajectories. By affirming the transformative potential of financial inclusion, this study not only contributes to the academic discourse but also provides a compelling case for policymakers to prioritize financial inclusion as a cornerstone of sustainable and equitable development in BRICS economies.